Analisis Kegrafikan Buku Teks Bahasa Indonesia untuk SMP Kelas VIII Kurikulum Merdeka - Sholikhah, Annisa Wakhidatus; Zahra, Nisrina Faradiva Az; Rahmadini, Farah Yuniar (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
This study aims to determine the graphical analysis of the Indonesian Language Textbook Class VIII Merdeka Curriculum compiled by Maya Lestari Gusfitri and Elly Delfia, published by the Center for Bookkeeping of the Ministry of Education, Culture, Research and Technology. This book is analyzed based on BSNP's graphical feasibility indicators, including book size and format, cover design, content design, typography, layout, illustrations, print quality, and binding. The research used a descriptive qualitative approach with a case study method. Data were collected through document observation and visual analysis, and analyzed using Clarke and Braun's six-step thematic method. The results showed that most of the graphical elements had met the eligibility standards, especially illustrations, typography, and layout that were in accordance with the characteristics of junior high school students. However, weaknesses were found in the binding aspect and limited illustrations that reflect local culture and linguistic values. This research is expected to be a reference for further studies as well as a consideration for teachers in choosing textbooks that are effective and suitable for learning.